Stress as a prestige marker in Singapore English - Soh, Ying Qi (Nanyang Technological University, 2023)
Past research has shown that suprasegmental features, such as intonation and stress, can be associated with social meanings and serve as prestige markers. In the context of Singapore English, studies on prestige have mainly focused on segmental features, highlighting the lack of attention given to the relationship between prestige and suprasegmental features like stress. This study aims to investigate whether stress can be a prestige marker in Singapore English. 36 tokens, divided equally among six disyllabic words, were electronically manipulated to mark stress using the acoustic correlates of fundamental frequency (F0), duration and intensity in order to serve as auditory stimuli. Data was collected from 44 Singapore English speakers through an online questionnaire, which asked participants to guess the stressed syllable of each token and to rate their attitudes towards the speaker along five criteria. Statistical analysis showed that participants were able to correctly identify the stressed syllable in a majority of cases, and that stress placement and the use of F0 to mark stress had a significant effect on the perceived prestige of a Singapore English speaker. The results of this study suggest that F0, not duration, is the most salient marker of stress in Singapore English, and that the use of F0 to mark stress could be an attempt to imitate British English norms and capitalise on the high prestige associated with that variety of English.